Empowerment of Catfish Breeding Business Actors in Villages Sidokepung Kec. Buduran Kab Sidoarjo: Pemberdayaan Pelaku Usaha Pembibitan Lele Di Desa Sidokepung Kec. Buduran Kab Sidoarjo - Jakaria, Ribangun Bamban; Hudi, Lukman; A. Miftakhurrahmat; Amelia K, Paramitha; Wisaksono, Arief; Sumarmi, Wiwik (Procedia of Social Sciences and Humanities, 2022)
Handoko, an independent nursery business actor in the village of Sidokepung, Kec Buduran, with a total of 7 nursery ponds with 2 broodstock ponds, makes the independent business developed relatively well. However, over time, the technology used in nurseries is considered outdated, this is because the seeding process carried out in nursery ponds causes many seeds that have been successfully bred to experience stress and not a few die, so the effectiveness of the seeding process is less effective. and it is necessary to apply technology to avoid stress on tillers during seeding. From these problems, firstly, the application of pond management technology has not been maximized by partners, which is marked by the number of deaths of catfish seedlings resulting from seeding, secondly, catfish chicks do not have the passion to eat due to lack of oxygen in the pond, third, pond water circulation is not carried out periodically. and contracted so that the pond water looks cloudy which causes the fish growth rate is not good, fourth, catfish chicks are difficult to grow and develop. The solution is the application of fish management technology by designing a pond by providing an aerator as a tool that functions to create air bubbles so as to guarantee the oxygen content in the pond has been met, creating a water reservoir that serves to provide a good supply of water in the pond, so that it will do the job well. periodic circulation of water in the pool and ensure the pool is clean and does not cause odor. the results obtained from solving problems, partners get better benefits and provide competitiveness in increasing the income of independent businesses that are carried out